2014
DOI: 10.1017/s095026881400301x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating seroprevalence of vaccine-preventable infections: is it worth standardizing the serological outcomes to adjust for different assays and laboratories?

Abstract: The aim of the European Sero-Epidemiology Network 2 (ESEN2) project was to estimate age-specific seroprevalence for a number of vaccine-preventable diseases in Europe. To achieve this serosurveys were collected by 22 national laboratories. To adjust for a variety of laboratory methods and assays, all quantitative results were transformed to a reference laboratory's units and were then classified as positive or negative to obtain age-specific seroprevalence. The aim of this study was to assess the value of stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…For instance, our study revealed that region 5, which contains Aichi, had the highest effective reproduction number at 2.48, and region 8 (Shikoku island, which is considerably aged compared with the five urbanized regions) yielded the lowest value at 1.01. Similar seroepidemiological evaluations have also been conducted elsewhere ( Pebody et al, 2000 , Kafatos et al, 2015 , Abrams et al, 2016 ). Additionally, accounting for the number of travelers, the highest probability of a major epidemic in our hypothetical scenario was estimated to be 1.00 in region 3, which includes Tokyo, and the lowest probability was estimated to be 0.01 in region 8.…”
Section: Discussionmentioning
confidence: 73%
“…For instance, our study revealed that region 5, which contains Aichi, had the highest effective reproduction number at 2.48, and region 8 (Shikoku island, which is considerably aged compared with the five urbanized regions) yielded the lowest value at 1.01. Similar seroepidemiological evaluations have also been conducted elsewhere ( Pebody et al, 2000 , Kafatos et al, 2015 , Abrams et al, 2016 ). Additionally, accounting for the number of travelers, the highest probability of a major epidemic in our hypothetical scenario was estimated to be 1.00 in region 3, which includes Tokyo, and the lowest probability was estimated to be 0.01 in region 8.…”
Section: Discussionmentioning
confidence: 73%
“…Estimates of the spatiotemporal dynamics of individual and population immunity to a variety of pathogens would be a powerful tool for public health programmes and will be facilitated by further improvements in laboratory assays to make them more user‐friendly in low‐income settings , standardising laboratory assays to make it easier to compare studies in different locations , continuing development of statistical approaches to analysing serological data including accounting for waning antibody levels over time , and studies to clarify the relationship between antibody levels, the number of doses of multidose vaccines received and the duration since the last dose.…”
Section: Discussionmentioning
confidence: 99%
“…The early loss of measurable antibody within a few years after a single priming dose in 8 noninfected children (8.3%) has been described for up to a third of adult travelers [14,15,21] and is somewhat higher than the results found in a large Argentinian study [22], in which antibody levels became unmeasurable within 5 years after a single priming dose in only 2.5% of children [22]. The somewhat variable course of the antibody levels in the vaccinated, noninfected children-falling slightly from 2005 to 2006 and then rising again to a maximum in 2007, before finally declining toward the trough level of 2012-may be ascribed to the fact that not all serum samples could be measured in parallel (see Methods), amplified by the assay variability inherent in immune assay testing [23].…”
Section: Discussionmentioning
confidence: 99%
“…Seronegativity was not retested before vaccination, leaving space to scrutinize whether all 25 HAV infections between 2003 and 2005 had occurred before vaccination; the anti-HAV IgM testing performed 3 months after vaccination showed, however, that the HAV infections detected serologically had most likely occurred before the first vaccination, because the infectioninduced, short-lived (3-6 months) anti-HAV IgM antibodies were either not measurable (n = 23) or borderline (n = 2) at this time point [4]. Although not all sequential serum samples obtained from each child could be tested in parallel, all anti-HAV measurements were done by the same expert (G. F.), using the same immune assay test system in the same laboratory, thus minimizing the variability inherent to anti-HAV antibody measurement with enzyme immune assays [23].…”
Section: Discussionmentioning
confidence: 99%